Perbandingan Aktivitas Antijamur dari Tanaman Syzygium terhadap Jamur Candida albicans - Alika Ismita; Umi Yuniarni; Siti Hazar (UNISBA Press, 2024)
Abstract. Candida albicans fungal infections are a common health problem, especially in individuals with weakened immune systems. Treatment is often hampered by drug resistance. This study aims to compare the antifungal activity of the Syzygium plant against the growth of Candida albicans in vitro. The research method used is the agar well diffusion method. The parameter measured is the formation of a clear zone around the well. The results showed that 3 plants had antifungal activity against Candida albicans. The diameter of the inhibition zone formed for the ethanol extract of red shoot leaves at a concentration of 1% was 12.95 mm, at a concentration of 5% was 14.525 mm, at a concentration of 10% was 14.175 mm, and at a concentration of 20% was 17 mm. For rose guava leaves at a concentration of 5% it was 12.825 mm, at a concentration of 10% it was 15.975 mm, and at a concentration of 20% it was 17.375 mm. Meanwhile, for kupa leaves at a concentration of 5% it was 11.425 mm, at a concentration of 10% it was 14.15 mm, and at a concentration of 20% it was 15.575 mm. Abstrak. Infeksi jamur Candida albicans merupakan masalah kesehatan yang umum, terutama pada individu dengan sistem kekebalan tubuh yang lemah. Pengobatannya seringkali terhambat oleh resistensi obat. Penelitian ini bertujuan untuk membandingkan aktivitas antijamur dari tanaman Syzygium terhadap pertumbuhan Candida albicans secara in vitro. Metode penelitian yang digunakan adalah metode difusi agar sumuran. Parameter yang diukur adalah terbentuknya zona bening di sekitar sumuran. Hasil penelitian menunjukkan bahwa 3 tanaman memiliki aktivitas antijamur terhadap Candida albicans. Diameter zona hambat yang terbentuk untuk ekstrak etanol daun pucuk merah pada konsentrasi 1% sebesar 12,95 mm, pada konsentrasi 5% sebesar 14,525 mm, pada konsentrasi 10% sebesar 14,175 mm, dan pada konsentrasi 20% sebesar 17 mm. Untuk daun jambu mawar pada konsentrasi 5% sebesar 12,825 mm, pada konsentrasi 10% sebesar 15,975 mm, dan pada konsentrasi 20% sebesar 17,375 mm. Sedangkan untuk daun kupa pada konsentrasi 5% sebesar 11,425 mm, pada konsentrasi 10% sebesar 14,15 mm, dan pada konsentrasi 20% sebesar 15,575 mm.